Global commodity markets and development economics - Pfaffenzeller, Stephan (Routledge studies in development economics, 2018)
"Global Commodity Markets and Development Economics brings together analyses from a number of perspectives in order to explore commodity price developments. Chapters explore long term commodity trends, the evolution of relative price developments, the relationship of the domestic commodity sector with global supply chains, agri-food prices, and the role of oil markets in the global economy. Through considering a diverse range of countries including China, Russia and the United States, the authors examine key fuel and non-fuel commodity markets and offer a window into important trends and developments."--Provided by publisher.